Франшиза в Україні: проблеми та шляхи вирішення - Стеців, І. С.; Стеців, І. І.; Stetsiv, I. S.; Stetsiv, I. I. (Видавництво Львівської політехніки, 2019)
Обґрунтовано актуальність досліджень проблем вибору франшизи. Досліджено стан та проблеми вибору франшизи, виявлено, що одним із факторів впливу на сповільнення поширення франшиз та їх закриття в Україні є відсутність обґрунтованої методики вибору франшизи. Досліджено переваги та недоліки започаткування бізнесу на снові франшизи. Визначено перешкоди, які негативно пливають на можливість ефективного організування бізнесу на основі франшизи. Розроблено обґрунтовану методику вибору франшизи в сучасних умовах господарювання. Доведено, що запропонована методика сприяє здійсненню обґрунтованої оцінки стану франчайзингових підприємств потенційними інвесторами та підвищує надійність та перспективність рішення щодо вибору бізнесу.

We substantiated the relevance of research into franchise choices. you have analyzed literary sources that highlight this issue and found that the focus of the scholars' attention is on issues related to the activities of franchise companies as franchisees. We have proved that a significant part of problem issues also arises from potential investors who invest in franchising companies that need research. We also explored the state and problems of franchise selection, and found that one of the factors influencing the slowdown of the spread of franchises and their closure in Ukraine is the lack of a sound methodology for choosing a franchise. We explored the advantages and disadvantages of starting a business on a franchise. A significant part of the franchisees' benefits to doing business is more likely to be promotional slogans to attract a broader audience of potential franchisees than real benefits that guarantee success in business, and the deficiencies described are not specific to the franchise or contain a high risk. At the same time, the disadvantages that pose real threats to potential franchisees remain out of the question. In particular, they can be considered as an insignificant opportunity to evaluate the franchise market and the financial and economic state of the franchisor's business because of the lack of a scientifically based approach to the choice of franchise. We identified a number of obstacles that stop the entrepreneurs from doing business with a franchise. The greatest difficulties are due to the lack of knowledge of entrepreneurs about the possibilities of this way of doing business. We have developed a sound method for choosing a franchise in today's business environment, which includes five steps towards a choice, namely the study of the market attractiveness of franchising enterprises, the assessment of the competitive environment of the franchise companies operating in the chosen market, the analysis of the financial state of the franchise business, the evaluation of the effectiveness of the franchise acquisition and the actual choice. We have proved that the proposed methodology allows potential investors to make a reasoned assessment of the state of the franchise business and to choose from a large number of options a reliable and promising business that can be initiated through such a model of business organization as a franchise. Today's implementation of the proposed methodology is complicated by the lack of access to reliable information and requires a transition to a new stage of globalization focused on the continuous formation of an array of data, representing an unlimited cyberspace, formed into a single whole for solving social problems and creating conditions for sustainable economic growth that requires further research.
Franchises in Ukraine: problems and ways for their decision
Keywords: франшиза; франчайзинг; франчайзі; фінансово-економічний стан; ринкова привабливість франчайзера; franchise; franchising; franchisee; financial and economic condition; franchisor market attractiveness; 378.014.5; 339.138